High Definition Metrology Based Surface Quality Control and Applications - Du, Shichang; Xi, Lifeng (Springer Nature Singapore : Imprint: Springer, 2019)
This book provides insights into surface quality control techniques and applications based on high-definition metrology (HDM). Intended as a reference resource for engineers who routinely use a variety of quality control methods and are interested in understanding the data processing, from HDM data to final control actions, it can also be used as a textbook for advanced courses in engineering quality control applications for students who are already familiar with quality control methods and practices. It enables readers to not only assimilate the quality control methods involved, but also to quickly implement the techniques in practical engineering problems. Further, it includes numerous case studies to highlight the implementation of the methods using measured HDM data of surface features. Since MATLAB is extensively employed in these case studies, familiarity with this software is helpful, as is a general understanding of surface quality control methods.